Regime diferenciado de contratações: uma análise de contratos em uma empresa pública - Jaqueline Vilela Araújo Paim (2015)
The traditional model of public procurement, regulated by the General Law of Bids - LGL - is criticized. The government was faced with challenges involving actions to improve its infrastructure, given that Brazil was chosen as a country leading global sporting events established in the years 2013, 2014 and 2016. The Differentiated Regime of Public Procurement - RDC - was created in order to bring speed and efficiency to public contracts and with the main objective of enabling, in a timely manner, the implementation of the necessary infrastructure for carrying out such events. This work, empirical, exploratory and qualitative approach aimed to verify that the RDC was more efficient to Infraero compared to LGL, including with regard to contracts and could be a way to substitute bid to LGL, no longer exclusive to specific events. The study used the case study as a research strategy. The unit of analysis is the RDC in Infraero and to meet the proposed objective to verify the efficiency of this new procurement regime to that public company, two of its bids and contracts were analyzed. We also used interviews, participant observation and document analysis in Infraero and interview in a Court of Auditors, external control body. As part of the methodology, it was created simulations in order to verify that the replacement of one form of bidding by the other brings reduction of the bidding time. It was verified, through simulations, that the bid by the RDC is more responsive than the bid by LGL. The time spent by the bidding committee is also lower when the bid is made by RDC. For contracts, the result of the competition was not feasible, it was not executed within the contractual term and is paralyzed. If resumed, there will be an increase of over 20% in contract value, which had been adjusted by nearly 7% of the contracted initial value. The result of the RDC can be considered feasible, it was not added and its services were provided by the end of the contract execution within the deadline. It was noticed that in connection with contract oversight there is no change in the DRC and the opinion of the external body control is different from the opinion of Infraero in relation to their stage of development, especially for contracts.